Multi-objective optimization of the floor plan of a single story family house considering position and orientation. (March 2020) - Zawidzki, Machi; Szklarski, Jacek
Highlights: A new method for enhancing architectural design in the early stage is presented. Coarse-grid layout optimization is extended with new global site-specific objectives. Psychological factors: acoustic & visual comfort introduced as optimization criteria. Novel general formal framework as architectural design aid is presented & discussed. Case study of multiobjective optimization of single-story building on given site. Abstract: Improving the architectural layout for diverse objectives using rigorous mathematical optimization methods gradually receives more attention by the researchers. Such optimization however, is usually reduced to a much simpler and relatively well-defined problem such as: facility layout optimization, quadratic assignment problem, rectangle partitioning. Nonetheless, architects are usually skeptical about such approaches since they produce solutions which lack certain architectural qualities. This paper proposes a framework where architectural functional layout (FL) is optimized for the following objectives: functionality (defined by users), insolation (calculated according to geographical conditions), outside view attractiveness (assessed on-site) and external noise (measured on-site). Incorporating the latter two and simultaneous optimization of FLs for objectives related specifically to the site: position and orientation are the novel contributions of this paper. Firstly, a set of candidate FLs is generated, next they are evaluated for optimal location and orientation on a given site. Optimality is conceived here as maximization of real-valued objective function combining: user's satisfaction level of the outside views, shielding from external noise, and insolation preference. The importance of these factors for each type of room is assessed by the user (as weights). A case study on an existing site is presented. The view quality was arbitrarily assessed and the noise map was assessed by A-weighted equivalent sound level measurements. A general gradient-based method for finding optimal and near-optimal solutions was applied. The output of this optimization is a set of room configurations with their locations and orientations on the site returned to the user for final selection.